Surveillance of Neisseria meningitidis carriage four years after menACWY vaccine implementation in the Netherlands reveals decline in vaccine-type and rise in genogroup e circulation - Miellet, Willem R.; Pluister, Gerlinde; Sikking, Meike; Tappel, Marcia; Karczewski, Jurgen; Visser, Linda J.; Bosch, Thijs; Trzciński, Krzysztof; Mariman, Rob (Vaccine, 2023)
Carriage of Neisseria meningitidisis an accepted endpoint in monitoring meningococcal vaccine effects. We applied molecular methods to assess the impact of menACWY vaccine implementation on meningococcal carriage and genogroup-specific prevalence in young adults in Fall of 2022, four years after the introduction of the tetravalent vaccine in the Netherlands. The overall carriage rate of genogroupable meningococci was not significantly different compared to a pre-menACWY cohort investigated in 2018 (20.8 % or 125 of 601 versus 17.4 % or 52 of 299 individuals, p = 0.25). Of 125 carriers of genogroupable meningococci, 122 (97.6 %) were positive for either vaccine-types menC, menW, menY or genogroups, menB, menE, and menX, which are not targeted by the menACWY vaccine. Compared with a pre-vaccine-implementation cohort, there was 3.8-fold reduction (p < 0.001) in vaccine-type carriage rates and 9.0-fold increase (p < 0.0001) in non-vaccine type menE prevalence. We observe a reduction in menW and menY and an increase in menE, which suggest that implementation of menACWY vaccine affected carriage.